2020
DOI: 10.21203/rs.3.rs-79442/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Colorectal Cancer Incidence and Mortality Trends by Sex and Population Group in South Africa: 2002-2014.

Abstract: BackgroundSouth Africa (SA) has experienced a rapid transition in the Human Development Index (HDI) over the past decade, which had an effect on the incidence and mortality rates of colorectal cancer (CRC). This study aims to provide CRC incidence and mortality trends by population group and sex in SA from 2002 to 2014.MethodsIncidence data were extracted from the South African National Cancer Registry and mortality data obtained from Statistics South Africa (STATS SA), for the period 2002 to 2014. Age-standar… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…68 In SSA, only South Africa has a national CRC database, and this data is limited to pathology reports and does not contain data on stage or survival. 69…”
Section: Colorectal Research In Lmicsmentioning
confidence: 99%
“…68 In SSA, only South Africa has a national CRC database, and this data is limited to pathology reports and does not contain data on stage or survival. 69…”
Section: Colorectal Research In Lmicsmentioning
confidence: 99%
“…South Africa has the highest incidence of colorectal cancer in SSA among men and women (3). There is an extensive literature on CRC incidence estimation [see, for example (4)(5)(6)]. However, little work has been done on CRC prognosis.…”
Section: Editorial On the Research Topic Application Of Biostatistics...mentioning
confidence: 99%
“…Recent increases in colorectal cancer incidence rates in South Africa, especially in younger patients, have paralleled increases in socioeconomic changes among ethnic groups. 7 Others have recently suggested that as countries develop economically, the types of cancers observed also evolve from those that are infection-related to those that are not infection-related. 1 These recent trends in cancer epidemiology compel the need for urgent action.…”
mentioning
confidence: 99%